In pursuit of national interest: change and continuity in Malaysia’s foreign policy towards the middle east - Ruhanas Harun (Institut Kajian Rantau Asia Barat, 2009)
Malaysia’s foreign policy has traditionally been focussed on Southeast Asia and its friends in the West. As such, the Middle East was not a priority area in its foreign policy despite the long established historical, social and religious connections that the country had with the region. It was not until the 1980s that Malaysia began to develop closer cooperation with the Middle East within the framework of strengthening relations with the Islamic world. Bilateral relations remained close with several countries of the region, although they lacked the visibility and force in comparison with Malaysia’s relations with East Asian countries and the West. This paper examines Malaysia’s contemporary foreign policy towards the Middle East,the factors shaping it, the issues and challenges in managing its relations with the region. It argues that Malaysia’s objectives in the Middle East are tied to securing its national interests that can be achieved by enhancing political, economic and social ties with the countries of the region. As a small country, Malaysia does not have the influence to affect events in the region. However, there are mechanisms and frameworks as well as the social and religious links that can help promote the country’s national interests. The paper further argues that while there are reasons to continue with the current policy towards the Middle East, Malaysia needs to take stock of the successes and failures of its relations with the countries of the region, and to explore some areas outside those traditional ones so as to take advantage of the economic opportunities that the region may provide.